The Effect of Twin Date Event, Price Discount, and Free Shipping on Impulsive Buying in Shopee Marketplace Reviewed in Islamic Business Perspective - Raihani Fauziah Khaerunnisa; Hanif Hanif; Nurhayati Nurhayati (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine the twin Date event, discount price and free shipping on impulsive buying partially and simultaneously as well as reviewing the perspective of Islamic Business. The research method used is a descriptive method with a quantitative approach, the population of this study is Generation Z in Bandar Lampung totaling 296.828 thousand inhabitants and a sample of 100 respondents. The results showed that the twin Date event had a positive and significant effect on impulsive buying, price discounts had a positive and insignificant effect on impulsive buying, free shipping had a positive and significant effect on impulsive buying and simultaneously the Twin Date Event, price discounts, and free shipping had a positive and significant effect on impulsive buying in the shopee marketplace in Generation z in Bandar Lampung City. Viewed from the perspective of Islamic Business, islam forbids excessive consumption behavior (isrāf) and waste (tabdzir) and must emphasize the principles of simplicity (al-iqtisād), balance (wasathiyah), and usefulness in consumption.